Multi-objective unit commitment with spinning reserve cost using hybrid method - Vatambeti, Rajasekhar; Dhal, Pradyumna Kumar (Institute of Advanced Engineering and Science, 2023)
Under the generation of electrical power, fuel consumption, and emission are emphasized in the thermal power industry. Based on this, emission and cost were considered objectives with inequality and equality constraints. The spinning reserve was replenished as one of the constraints. In this paper, the spinning reserve cost (SRC)was incorporated with the total cost objective function. The hybrid technique is steered to achieve minimal value which is the combination of the cuckoo search method and flower pollination algorithm. To predict the potential of the proposed technique, two systems are considered namely a four-unit system and an IEEE thirty-nine bus system. The obtained simulation outcome shows a better improvement with the proposed technique in optimal value.